Cooking the books: Recipes and costs of falsified financial statements in China - Firth, Michael; Rui, Oliver M.; Wu, Wenfeng (Journal of Corporate Finance, 2011)
We examine the causes and consequences of falsified financial statements in China. Using bivariate probit regression analysis, we find that firms with high debt and that plan to make equity issues are more likely to manipulate their earnings and thus have to restate their financial reports in subsequent years. We also find that corporate governance structures have an effect on the occurrence and detection of financial fraud. There are significant negative consequences to fraudulent financial statements. Restating firms suffer negative abnormal stock returns, increases in their cost of capital, wider bid–ask spreads, a greater frequency of modified audit opinions, and greater CEO turnover. We also find that firms located in highly developed regions suffer more severe consequences when they manipulate their accounts.